2016
DOI: 10.1016/j.rmed.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants of SERPIN1A gene: Interplay between alpha1-antitrypsin deficiency and chronic obstructive pulmonary disease

Abstract: Alpha1-antitrypsin (AAT) is one of the major circulating anti-protease whose levels in circulation are raised during excessive amount of proteases, especially neutrophil elastase (NE) released during the course of inflammation. Proteolytic attack of NE on peripheral organs, more exclusively on lung parenchyma has severe consequence that may precipitate pulmonary emphysema. Normally, human body has its own molecular and physiological mechanisms to synthesize and regulate the production of anti-protease like AAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 83 publications
(57 reference statements)
1
21
0
1
Order By: Relevance
“…AAT is an important anti-protease in the lung, but it also has significant anti-inflammatory effects on several cell types and modulates inflammation caused by host and microbial factors. In effect, it can play an important role in modulating key immune cell activities and protecting the lungs against damage caused by proteases and inflammation.REVIEW a 1 -ANTITRYPSIN DEFICIENCY Accumulation of ZAAT in the rough endoplasmic reticulum of hepatocytes leads to reduced availability of AAT in the circulation, and thus AAT is insufficient to neutralise the excessive amount of protease synthesised, especially in the lungs during the course of inflammation [3]. Presence of Z-polymer in the circulation and in bronchoalveolar lavage fluid of patients with severe AATD generates a substantial concentration dependent influx of neutrophils that is not driven by chemokines.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…AAT is an important anti-protease in the lung, but it also has significant anti-inflammatory effects on several cell types and modulates inflammation caused by host and microbial factors. In effect, it can play an important role in modulating key immune cell activities and protecting the lungs against damage caused by proteases and inflammation.REVIEW a 1 -ANTITRYPSIN DEFICIENCY Accumulation of ZAAT in the rough endoplasmic reticulum of hepatocytes leads to reduced availability of AAT in the circulation, and thus AAT is insufficient to neutralise the excessive amount of protease synthesised, especially in the lungs during the course of inflammation [3]. Presence of Z-polymer in the circulation and in bronchoalveolar lavage fluid of patients with severe AATD generates a substantial concentration dependent influx of neutrophils that is not driven by chemokines.…”
mentioning
confidence: 99%
“…Presence of Z-polymer in the circulation and in bronchoalveolar lavage fluid of patients with severe AATD generates a substantial concentration dependent influx of neutrophils that is not driven by chemokines. Furthermore, ZAAT creates endoplasmic reticulum stress in the hepatocytes, which may have severe consequences in the liver ranging from liver cirrhosis to hepatocellular carcinoma directly [3].The rarer null variants that include a variety of gene insertions, deletions and point mutations can result in the absence of AAT production, and null heterozygotes can appear to be normal (M null ) or abnormal (Z null ) based on the electrophoretic pattern of protein phenotyping, although not consistent with expected According to the ERS statement, annual measurement of lung function including post-bronchodilator FEV 1 and gas transfer provides information about disease progression [4].Chest CT scanning in those with AATD According to the US Alpha-1 Foundation, in newly diagnosed patients who are symptomatic and/or have abnormal pulmonary function testing, a baseline CT scan of the chest is recommended, whereas serial chest CT scanning to monitor progression of disease is not recommended [31].According to the ERS statement, lung densitometry, as performed in observational cohort studies and randomised clinical trials, is the most sensitive measure of emphysema progression [4]. Although the correlation between change in lung density and any short-term change in measures of pulmonary function is weak, in the longer term, CT lung density decline correlates with reduction in FEV 1 and health status.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic factors, either inherited or epigenetic, contribute to the development of respiratory diseases such as asthma, chronic obstructive pulmonary disease (COPD), lung cancer and cystic fibrosis, in addition to environmental exposures . For example, genetic studies have identified genetic variants associated with respiratory diseases, such as SERPINA1 mutations in COPD causing alpha‐1 antitrypsin deficiency, mutations in the CFTR gene in cystic fibrosis and a number of single nucleotide polymorphisms (SNP) associated with asthma and allergy phenotypes . Given the importance of genomics in the pathogenesis of many common respiratory diseases, a better understanding of the pathogenic consequences of genetic variation—and how to overcome genetic alterations—is urgently needed in order to achieve better diagnosis, prevention and treatment for people with or at risk of respiratory diseases.…”
Section: Genes and Respiratory Diseasementioning
confidence: 99%